Exploring dentists’ experiences of endodontic file fracture during root canal treatment: a phenomenological study - Mohammad Rastegar Khosravi; Zhina Banafshi; Rayan Ebrahimi; Rostam Jalali (BMC Oral Health)
Abstract Objectives File fracture represents a common and occasionally unavoidable occurrence during root canal procedures, carrying substantial negative implications for dental practitioners. This study explores dentists’ encounters with file fracture incidents during root canal treatment. Methods In this qualitative study using a phenomenological approach, 13 dentists were included through purposive sampling. The sampling continued until data saturation and semi-structured in-depth interviews were used to collect data. The 7-step Colaizzi approach was employed to analyze the collected data, and Lincoln and Guba’s criteria were used to ensure data credibility. Results The participant cohort comprised eight male and five female dentists, boasting an average of 10.15 ± 5.35 years of professional experience and an average age of 36.53 ± 6.35 years. Data segmentation revealed four themes alongside 18 sub-themes. These themes encompassed the fear of consequences, professional impasse, Integration decline, and the dilemma between moral and immoral decision-making. Conclusion The experiences of dentists during file fracture showed Fear of Consequences, Professional Impasse, Integration Decline, and the Dilemma between Moral and Immoral Decision-Making. File fracture episodes are distressing and taxing for dentists, harboring significant personal and professional repercussions. Such incidents precipitate emotional strain, compromise treatment efficacy, tarnish professional standing and identity, result in financial setbacks, and contribute to professional burnout. Consequently, policymakers must implement several measures, including strengthening legal and insurance protections, establishing secure reporting systems, developing a comprehensive, standardized, and practical document by the endodontic association, and mandating informed consent forms.